2015
DOI: 10.1073/pnas.1507317112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis for the specific recognition of the metazoan cyclic GMP-AMP by the innate immune adaptor protein STING

Abstract: Cyclic GMP-AMP containing a unique combination of mixed phosphodiester linkages (2′3′-cGAMP) is an endogenous second messenger molecule that activates the type-I IFN pathway upon binding to the homodimer of the adaptor protein STING on the surface of endoplasmic reticulum membrane. However, the preferential binding of the asymmetric ligand 2′3′-cGAMP to the symmetric dimer of STING represents a physicochemical enigma. Here we show that 2′3′-cGAMP, but not its linkage isomers, adopts an organized free-ligand co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(68 citation statements)
references
References 27 publications
0
66
2
Order By: Relevance
“…High affinity nvSTING–3′,3′ CDN interactions are made possible by a phenylalanine at the hSTING position 236, allowing a type of nucleobase stacking not possible with mammalian STING alleles. The uniquely compact regiochemical conformation of 2′,3′ cGAMP (Shi et al, 2015) allows it to target a more intermediately rotated state of STING where R238, a key residue involved in base-specific nvSTING–3′,3′ CDN, now completes the nucleobase stacking (Figure 6). It is possible that subsequent to the evolution of 2′,3′ cGAMP, F236 was lost to enhance discrimination of endogenous mammalian 2′,3′ cGAMP from bacterial 3′,3′ CDNs.…”
Section: Discussionmentioning
confidence: 99%
“…High affinity nvSTING–3′,3′ CDN interactions are made possible by a phenylalanine at the hSTING position 236, allowing a type of nucleobase stacking not possible with mammalian STING alleles. The uniquely compact regiochemical conformation of 2′,3′ cGAMP (Shi et al, 2015) allows it to target a more intermediately rotated state of STING where R238, a key residue involved in base-specific nvSTING–3′,3′ CDN, now completes the nucleobase stacking (Figure 6). It is possible that subsequent to the evolution of 2′,3′ cGAMP, F236 was lost to enhance discrimination of endogenous mammalian 2′,3′ cGAMP from bacterial 3′,3′ CDNs.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is well known that 2′3′‐cGAMP binds to STING with higher affinity than other linkage isomers like 2′2′‐cGAMP, 3′2′‐cGAMP and 3′3′‐cGAMP, structural studies clearly showed that cGAMPs bind to STING with indistinguishable modes. Recent data demonstrated that only inactive free‐ligand 2′3′‐cGAMP adopts an organized and favorable conformation which is more similar to the STING‐bound conformation owing to its specific G(2′,5′)pA phosphodiester linkage, thus it requires low entropy and enthalpy costs in converting into the active conformation . Besides natural 2′3′‐cGAMP, modified cGAMP linkages such as 2′3′‐cG s A s MP, a hydrolysis‐resistant bisphosphothioate analog of 2′3′‐cGAMP, was reported to retain even stronger STING agonist activity than 2′3′‐cGAMP .…”
Section: Identification and Characterization Of The Cgas‐cgamp‐sting mentioning
confidence: 99%
“…RIG-I 11 and melanoma differentiation-associated protein 5 (MDA5) 12 can recognize viral dsRNA and recruit the CARD containing adaptor protein MAVS (also known as IPS-1, CARDIF or VISA), leading to IRF activation and the production of type I IFN. In addition to RLRs, a group of cytosolic DNA sensors such as cyclic GMP-AMP synthase (cGAS), [13][14][15] absent in melanoma 2 (AIM2), 16,17 DDX41, 18,19 Rad50, 20,21 LRRFIP1, 22 DNA-dependent activator of IRFs (DAI), 23 as well as various RNA sensors such as IFN-induced protein with tetratricopeptide repeats 1 (IFIT1) 24 also play potent roles in inducing antiviral immune response, respectively via the adaptor protein stimulator of interferon genes (STING, also known as MITA, ERIS or MPYS) or the MAVS pathway. cGAS, which was previously thought to recognize cytoplasmic dsDNA over 40 bp in a sequence-independent manner, is recently shown to recognize unpaired guanosines flanking short (12-20 bp) dsDNA (Y-form DNA) found in human immunodeficiency virus type 1 to induce type I IFN production.…”
Section: Introductionmentioning
confidence: 99%